Development of a Web-Based AHP Decision Support System for Foster Child Character Evaluation - Yuli Haryanto; Amir Karimi (Ali Institute of Reseach and Publication, 2025)
In an era of rapidly developing technology - especially among the millennial generation - the need for a fast yet simple and practical system has increased significantly. The Indonesian Independent Golden Generation Foundation, a social institution in Bekasi, has been facing challenges in managing data and determining the character of foster children which is being done manually and without a proper structure. This research aims to develop an application to determine the character of foster childrens using the Analytical Hierarchy Process (AHP) method. This application is designed to overcome problems of efficiency and accuracy in data management and to determine the character of foster childrens. The AHP method is used to break down complex problems into a hierarchically arranged components, using weighted comparisons for decision making. The research results show that this application can simplify the performance of the foundation administrators, speed up the process of determining the character of a foster children more objectively, and reduce subjectivity in decision making. There is criterias considered that includes honesty, independence, respect, creativity and discipline. This application is expected to be able to provide an effective solution for foundations in managing foster child data efficiently and accurately.